2020
DOI: 10.1371/journal.pone.0241229
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for development of acute kidney injury in hospitalised adults in Zimbabwe

Abstract: Background Acute kidney injury (AKI) is predominantly a disease of low and middle-income countries. Despite this, there is a particular paucity of data regarding AKI in Africa. Most published studies were conducted prior to the most recent Kidney Disease: Improving Global Outcomes (KDIGO) definition of AKI. This prospective, observational, cohort study examines AKI amongst newly admitted acute medical inpatients in a large, urban, tertiary hospital in Harare, Zimbabwe. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 25 publications
3
15
0
Order By: Relevance
“…In Benin, Vigan et al showed that AKI was present in 11.8% of all adult admissions in two large hospitals in Cotonou [ 31 ]. In a prospective cohort of 253 Zimbabwean adults newly admitted to a large tertiary hospital in Harare, Gilbert et al recorded 14.2% AKI [ 32 ]. In Malawi, Evans et al in a prospective study of general medical admissions to a tertiary hospital in Blantyre found 17.2% of patients with AKI [ 33 ].…”
Section: Incidence and Prevalence Of Aki In Sub-saharan Africamentioning
confidence: 99%
See 4 more Smart Citations
“…In Benin, Vigan et al showed that AKI was present in 11.8% of all adult admissions in two large hospitals in Cotonou [ 31 ]. In a prospective cohort of 253 Zimbabwean adults newly admitted to a large tertiary hospital in Harare, Gilbert et al recorded 14.2% AKI [ 32 ]. In Malawi, Evans et al in a prospective study of general medical admissions to a tertiary hospital in Blantyre found 17.2% of patients with AKI [ 33 ].…”
Section: Incidence and Prevalence Of Aki In Sub-saharan Africamentioning
confidence: 99%
“…Male sex appears to be a risk factor for AKI in most African studies [ 8 , 32 , 38 ]. The fact that male patients predominate in African series is often attributed by some authors to poor access of females to health care.…”
Section: Factors Associated With Aki In Sub-saharan Africamentioning
confidence: 99%
See 3 more Smart Citations